Time to Reach Full Enteral Feeding and Its Predictors among Very Low Birth Weight Neonates Admitted in the Neonatal Intensive Care Unit: A Follow-Up Cohort Study - Belay Alemayehu Getahun; Sileshi Mulatu; Hailemariam Mekonnen Workie (Journal of Nutrition and Metabolism)
Background. Feeding is crucial for very low birth weight neonates to grow and develop properly. This study aims to determine the time to achieve full enteral feeding and predictors among neonates admitted at Felege Hiwot Comprehensive Specialized Hospital. Methods. An institutional retrospective follow-up study design was conducted among 332 very low birth weight neonates from July 1, 2018, to June 30, 2021. Samples were selected through a computer-generated simple random sampling method, and the data were entered into Epi data version 4.6 and then exported to STATA version 16 for analysis. Kaplan–Meier with the log-rank test was used to test for the presence of difference in survival among predictor variables. Model goodness of fit and assumptions were checked by the Cox–Snell residual and the global test, respectively. Variables with p value <0.25 in the bi-variable analysis were fitted to the multivariable Cox-proportional hazard model. Finally, the adjusted hazard ratio (AHR) with 95% CI was computed, and variables with a p value less than 0.05 in the multivariable Cox regression analysis were considered significant predictors of time to reach full enteral feeding. Results. A total of 332 neonates were followed for 2,132 person days of risk time and 167 (50.3%) of very low birth weight neonates started full enteral feeding. The overall incidence rate of full enteral feeding was 7.8 per 100 person day observations. The median survival time was 7 days. Very low birth weight neonates delivered from pregnancy-induced hypertension-free mothers (AHR: 2.1; 95% CI: 1.12, 3.94), gestational age of ≥33 weeks (AHR: 5,; 95% CI: 2.29, 11.13), kangaroo mother care initiated (AHR: 1.4; 95% CI: 1.01, 2.00), avoiding prefeed residual aspiration (AHR: 1.42; 95% CI: 1.002–2.03), and early enteral feeding (AHR: 1.5; 95% CI: 1.03, 2.35) were significant predictors of full enteral feeding. Conclusions. According to this study, the time to achieve full enteral feeding was relatively short. Therefore, healthcare professionals should emphasize achieving full enteral feeding and address hindering factors to save the lives of VLBW neonates.